Dermoscopic patterns in patients with a clinical diagnosis of onychomycosis—results of a prospective study including data of potassium hydroxide (KOH) and culture examination - Miriam América Jesús-Silva (Mattioli1885, 2015)
Background: Onychomycosis is the most common nail disease, representing 50% of cases affecting the nail apparatus. The diagnosis is made by clinical examination along with the KOH exam of the nail and culture of the sample. However, not all dermatologists have access to a mycology lab.